Students Conceptions of Chemical Bonds in the Context of Graphene - V Seftari; A Supriatna; T Widhiyanti (Pascasarjana Universitas Pendidikan Indonesia, 2020)
This study aims to determine students understanding of the concepts related chemical bonds in the context of graphene. Data collection of this qualitative study were conducted using open-ended test and interview methods. The participants consisted of 30 students in 2nd grade high school who had studied chemical bonds. This study is related to students understanding of the formation of bonds between C atoms in graphene, the relationship of chemical bonds to graphene material strength, the movement of electrons that can conduct electricity to graphene. This research obtained that most students were unable to apply the concept of chemical bonds in the context of graphene. This is because the context of graphene has never been used as an example in the concept of chemical bonds in chemical learning. So the context of graphene is unfamiliar to students.